Microbial inoculum production for biocrust restoration: testing the effects of a common substrate versus native soils on yield and community composition. (28th February 2020) - Ayuso, Sergio Velasco; Giraldo‐Silva, Ana; Barger, Nichole N.; Garcia‐Pichel, Ferran
Abstract : Human activities are causing unprecedented disturbances in terrestrial ecosystems across the globe. To reverse soil deterioration in drylands, a promising tool is the ex situ cultivation of biological soil crusts, topsoil geobiological assemblages that provide key ecosystem services. One approach is to transplant biocrusts cultivated in greenhouse nursery facilities into degraded sites to accelerate recovery. Lichen‐ and moss‐dominated biocrusts have been successfully grown using a common, sandy soil. We compared the use of a common, sandy soil versus native soils as a substrate for the cultivation of cyanobacteria‐dominated biocrusts. In greenhouse experiments, we inoculated natural biocrusts collected from three Southwestern USA dryland sites on to either a common, sandy soil or on their respective native soils. The common substrate resulted in a moderate enhancement of growth yield relative to native soils. While changes in bacterial phyla composition remained low in all cases, the use of a common substrate introduced larger shifts in cyanobacterial community composition than did using native soils. The shift increase attributable to the common, sandy soil was not catastrophic—and typical cyanobacteria of field biocrusts remained dominant—unless textural differences between the common substrate and native soils were marked. Because collecting native soils adds a significant effort to growing cyanobacterial biocrusts in greenhouses for restoration purposes, the use of a common, sandy substrate may be considered by land managers as a standard practice. But we recommend to regularly monitor the composition of the grown biomass.